SP0143 A new day for people with psoriatic arthritis: a heterogeneous disease that can be treated well?. (15th June 2017) - Coates, LC
Abstract : This talk will summarise recent advances in research around the treatment of psoriatic arthritis (PsA). Firstly there will be an update on research that shows the importance of treating patients promptly when they are diagnosed. Then results from studies of new therapies for both psoriasis and psoriatic arthritis will be shown to highlight the drugs that have recently become available in the clinic or are likely to be become available in the next few years. This will include new biologic disease modifying drugs with different targets including those that target interleukin 17 and interleukin 23 as well as new oral medications that are part of a family called small molecules. The role of these new therapies and how they compare to existing therapies in the clinic will be addressed. Finally there will be a summary on the research of how to use the existing and new therapies in the clinic including the use of the "treat to target" strategy. Disclosure of Interest: L. Coates Grant/research support from: Abbvie, Janssen, Consultant for: Abbvie, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sun Pharma, UCB